Bismuth encephalopathy- a rare complication of long-standing use of bismuth subsalicylate - Borbinha, Cláudia (2019)
Background: Drugs containing bismuth, although usually safe, may rarely cause neurotoxicity. Case presentation: We describe the case of a 44-year-old woman treated with bismuth subsalicylate for about 20 years, who developed abnormal behaviour and postural instability in two weeks. On examination, she had greyish discoloration of teeth, was confused and presented generalized myoclonic jerks. In the next days, her clinical condition deteriorated, with a reduction in alertness and more exuberant myoclonus. Brain MRI was unremarkable. CSF revealed mild elevation of protein content (47 mg/dL; reference range: 15-45 mg/dL) and elevation of white blood cell count (10/μL). Bismuth levels in urine (375 μg/L), serum (260 μg/L) and CSF (21.4 μg/L) samples were highly above the threshold for toxicity. Following supportive treatment and bismuth discontinuation, she made a full recovery within weeks. Conclusions: Although rare, bismuth encephalopathy should be considered in patients presenting with subacute encephalopathy and myoclonus. This encephalopathy can be subacute even after a chronic exposure. Cessation of bismuth can lead to a complete resolution in weeks.